All the other mothers hate me : a novel [large type] - Harman, Sarah, 1986- (Random House Large Print, 2025)
"Florence Grimes is a thirty-one-year-old party girl who always takes the easy way out. Single, broke and unfulfilled after the humiliating end to her girl band career, she has only one reason to get out of bed each day: her ten-year-old son Dylan. But then Alfie Risby, her son's bully and the heir to a vast frozen food empire, mysteriously vanishes during a class trip, and Dylan becomes the prime suspect. Florence, for once, is faced with a task she can't quit: She's got to find Alfie and clear her son's name, or risk losing Dylan forever. The only problem? Florence has no useful skills, let alone investigative ones, and all the other school moms hate her. Oh, and Florence has a reason to suspect Dylan might not be as innocent as she'd like to believe..."--